2020
DOI: 10.1200/jco.2020.38.15_suppl.5518
|View full text |Cite
|
Sign up to set email alerts
|

A phase I, open-label, multicenter study to assess the safety, pharmacokinetics, and preliminary antitumor activity of AZD4635 both as monotherapy and in combination in patients with advanced solid malignancies: Results from prostate cancer patients (NCT02740985).

Abstract: 5518 Background: AZD4635 inhibits adenosine 2a receptor (A2aR) signaling and improves immune activation and anti-tumor activity in preclinical models. This phase I study assessed the safety, pharmacokinetics, pharmacodynamics and efficacy of AZD4635 monotherapy (mono) and in combination (combo) with durvalumab (durva) in patients (pts) with refractory solid tumors. Here we present data for immune checkpoint-naïve pts with metastatic castrate-resistant prostate cancer (mCRPC). Methods: Pts with refractory mCRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…87 As opposed to Open access checkpoint inhibitor response, this score was highly predictive of improved outcomes to A2AR blockade in a cohort of patients with mCRPC. 88 In assessing all tumors within TCGA, the adenosine signaling signature has a wide range of expression; and as with AdenoSig, there does not appear to be a consistently elevated score among the cancer types best studied for response to A2AR inhibition (NSCLC, RCC, melanoma, mCRPC). 86 Again, elucidation of additional biomarkers will be crucial for more accurate interpretation of this genomic signature moving forward.…”
Section: Clinical Data and Biomarker Investigationmentioning
confidence: 99%
“…87 As opposed to Open access checkpoint inhibitor response, this score was highly predictive of improved outcomes to A2AR blockade in a cohort of patients with mCRPC. 88 In assessing all tumors within TCGA, the adenosine signaling signature has a wide range of expression; and as with AdenoSig, there does not appear to be a consistently elevated score among the cancer types best studied for response to A2AR inhibition (NSCLC, RCC, melanoma, mCRPC). 86 Again, elucidation of additional biomarkers will be crucial for more accurate interpretation of this genomic signature moving forward.…”
Section: Clinical Data and Biomarker Investigationmentioning
confidence: 99%
“…AZD4635 was assessed as monotherapy or combined with durvalumab in advanced solid tumors (Figure 1). Results from a highly pretreated metastatic prostate cancer patient cohort were reported at ASCO 2020 [138]. The molecule was associated with a good safety profile but modest efficacy, with an ORR of 6.1% as monotherapy and 16.2% in combination.…”
Section: Extracellular Adenosinementioning
confidence: 99%
“…For instance, a phase I/II trial targeting CD38 (Isatuximab) and PD-1 (Cemiplimab) reported a manageable safety profile, reduction of CD38 + immune subsets in the tumor microenvironment, and enhanced activation of peripheral T cells, and that 20.8% and 65% of metastatic castration-resistant prostate cancer and non-small cell lung cancer (NSCLC) patients, respectively, achieved stable disease. 146 Phase I trials of CD73-targeting antibodies (Oleclumab) or A 2A AR antagonists (Ciforadenant, AZD4635) alone, or in combination with approved αPD-L1 checkpoint inhibitor antibodies (durvalumab, atezolizumab), showed manageable safety profiles, [147][148][149][150] and combination therapy of CPI-006 (αCD-73 antibody) and Ciforadenant was also well-tolerated. 151 Larger trials testing efficacy of A 2A AR inhibition and CD73 blockade are ongoing, and a dual A 2A AR/A 2B AR antagonist, etrumadenant, showed promising safety and PK/PD in a phase I clinical trial and is being evaluated further.…”
Section: Clinical Implications Of Immunosuppressive Metabolitesmentioning
confidence: 99%